Aktivitas Dakwah Majelis Taklim Rodiyatammardiyah dalam Membina Nilai-Nilai Keberagamaan Jamaah - Aulia Cangra Munggaran; Bambang Saiful Ma'arif; Muhammad Fauzi Arif (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Majlis taklim is a term for Islamic non-formal educational institutions that have their own curriculum, are held periodically and regularly, attended by a relatively large congregation. The taklim assembly includes non-formal education specifically in the field of religion, as a form of da'wah activity. The taklim assembly has activities such as conveying Islamic teachings in order to encourage people to always follow His path, as well as reciting or learning to read the Koran. The location of this research is RW 02 Pasirwangi Village, Ujungberung District, Bandung City. This research aims to find out the material presented and the da'wah methods used by the Rodiyatammardiyah Taklim Council da'iyah, as well as to find out the impact of the Rodiyatammardiyah Taklim Council's da'wah activities in fostering the religious values ​​of its congregation. Based on this phenomenon, the problem in this research is formulated as follows: (1) How does the Rodiyatammardiyah Taklim Council preach material in fostering its religious values? (2) What are the Da'wah methods used by the Rodiyatammardiyah Taklim Council in fostering the religious values ​​of its congregation? (3) What is the impact of the Rodiyatammardiyah Taklim Council's preaching on its congregation? The results of the research, the material presented and the methods used are the main things in the success of the da'wah activities of the Rodiyatammaridyah taklim assembly in fostering the religious values ​​of its congregation. The material presented includes reading the Al-Qur'an, aqidah, sharia, and others. The method used by da'iyah in their preaching is the mau'idzah hasanah method. The da'wah activities of the Rodiyatammardiyah Taklim Council in fostering its religious values ​​have shown a good impact, in increasing the congregation's interest in reading the Qur'an, increasing faith in Allah SWT through diligent worship, and the Rodiyatammardiyah Taklim Council congregation also feels that they have changed for the better. with the Da'wah Activities of the Rodiyatammardiyah Taklim Council. Abstrak. Majelis taklim adalah sebuah sebutan untuk lembaga pendidikan non-formal Islam yang memiliki kurikulum sendiri, diselenggarakan secara berkala dan teratur, diikuti oleh jamaah yang relatif banyak. Majelis taklim termasuk pendidikan non-formal yang khusus dalam bidang agama, sebagai salah satu bentuk kegiatan dakwah. Majelis taklim memiliki kegiatan seperti, penyampaian ajaran-ajaran Islam dalam rangka mengajak manusia selalu berada pada jalan-Nya juga adanya pengajian atau belajar membaca Al-Qur’an. Lokasi penelitian ini berada di RW 02 Kelurahan Pasirwangi, Kecamatan Ujungberung, Kota Bandung. Penelitian ini bertujuan untuk mengetahui materi yang disampaikan, dan metode dakwah yang digunakan da’iyah Majelis Taklim Rodiyatammardiyah, serta mengetahui dampak adanya Aktivitas dakwah Majelis Taklim Rodiyatammardiyah dalam membina nilai-nilai keberagamaan jamaahnya. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana materi dakwah Majelis Taklim Rodiyatammardiyah dalam membina nilai-nilai keberagamaannya? (2) Bagaimana Metode Dakwah yanag digunakan Majelis Taklim Rodiyatammardiyah dalam membina nilai-nilai keberagamaan jamaahnya? (3) Bagaimana dampak dakwah Majelis Taklim Rodiyatammardiyah terhadap jamaahnya?. Hasil dari penelitian, materi yang disampaikan dan metode yang digunakan menjadi hal utama dalam keberhasilan aktivitas dakwah majelis taklim rodiyatammaridyah dalam membina nilai-nilai keberagamaan jamaahnya. Materi yang disampaikan mencakup materi pembacaan Al-qur’an, akidah, syariah, dan lainya. Metode yang digunakan da’iyah dalam dakwahnya menggunakan metode mau’idzah hasanah. Aktivitas dakwah majelis taklim rodiyatammardiyah dalam membina nilai-nilai keberagamaannya menunjukan dampaik yang baik, dalam menigkatkan minat baca al-Qur’an para jamaah, meningkatkan keimanan kepada Allah SWT dengan beribadah yang rajin, juga jamaah Majelis Taklim Rodiyatammardiyah merasa berubah ke arah yang lebih baik dengan adanya Aktivitas Dakwah Majelis Taklim Rodiyatammardiyah ini.